2021
DOI: 10.3389/fnut.2021.688295
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Energy Balance Behaviors Are Associated With Greater Weight Loss During a Weight Loss Program

Abstract: Introduction: Free-living movement (physical activity [PA] and sedentary behavior [SB]) and eating behaviors (energy intake [EI] and food choice) affect energy balance and therefore have the potential to influence weight loss (WL). This study explored whether free-living movement and/or eating behaviors measured early (week 3) in a 14-week WL programme or their change during the intervention are associated with WL in women.Methods: In the study, 80 women (M ± SD age: 42.0 ± 12.4 years) with overweight or obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Relevant research can be divided into the following three categories. (1) Association of PA and diet with weight status: The results of several studies have indicated that intermittent fasting is beneficial for body weight, but diet-induced weight changes are generally short-lived and greater benefits can be gained through vigorous PA [ 11 , 12 ]. Bogataj et al have demonstrated that just 8 weeks of school-based high-intensity interval training with three sessions a week and nutrition intervention can improve upper body muscle and physical aerobic performance in adolescents and help reduce BMI in overweight girls [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research can be divided into the following three categories. (1) Association of PA and diet with weight status: The results of several studies have indicated that intermittent fasting is beneficial for body weight, but diet-induced weight changes are generally short-lived and greater benefits can be gained through vigorous PA [ 11 , 12 ]. Bogataj et al have demonstrated that just 8 weeks of school-based high-intensity interval training with three sessions a week and nutrition intervention can improve upper body muscle and physical aerobic performance in adolescents and help reduce BMI in overweight girls [ 13 ].…”
Section: Introductionmentioning
confidence: 99%